Understanding American politics and government - Coleman, John J. (Pearson, 2014)
Solve real-world puzzles like a political scientist Understanding American Politics and Government, 2012 Election Edition introduces students to the basic tools used by political scientists. It guides students through the fundamentals of government and helps them see why events really happen in politics. Consistently showing the difference between "causation" and "correlation," this text presents American government as a field full of interesting questions and puzzles that all citizens must explore. The book draws heavily on real-world politics to help students think more critically about their political beliefs and actions. This text features full integration with the New MyPoliSciLab. MyPoliSciLab includes a wide array of resources to encourage students to look at American politics like a political scientist and analyze current political issues. Political Explorer lets students play the role of a political scientist by investigating issues through interactive data. Core Concept videos discuss the big ideas in each chapter and apply them to key political issues. Simulations allow students to experience how political leaders make decisions. A better teaching and learning experience This program provides a better teaching and learning experience-for you and your students.